Generations of Achievement: The Family and Early Life of Orchid Ramsey Jordan in Clay Center, Kansas, 1910–1928 - Claxton, Haley (Kansas State University, The Chapman Center for Rural Studies, 2014)
Orchid Ramsey was a small-town African American girl born in 1910. She went on to marry Leon Jordan, a prominent Kansas City Civil Rights activist, and take over his position in Missouri’s General Assembly for sixteen years after his assassination. This project utilized resources from the Clay County Historical Society and the University of Missouri-Kansas City Miller Nichols Library.
Haley Claxton, “Generations of Achievement: The Family and Early Life of Orchid Ramsey Jordan in Clay Center, Kansas, 1910–1928,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/233.
Keywords: African Americans; civil rights movement; interracial marriage; Orchid Jordan; Wakefield; racial integration